Fungal Transformation and Oxalate-Mediated Mineralization of Heavy Metal Oxides by Aspergillus aculeatus - Thanakorn Sawangchart; Sutee Chutipaijit; Bunyarit Meksiriporn; Worapat Narueban; Worrathon Tilokkarn; Pattareewan Imsuwan; Thanawat Sutjaritvorakul (Journal of Xenobiotics, 2026)
PTW4, highlighting its potential relevance to fungal-mediated bioremediation and selective bioleaching processes.
Keywords: Microbial Applications in Construction Materials; Metal Extraction and Bioleaching; CO2 Sequestration and Geologic Interactions